The effect of non performing financing volume with inflation as moderating variables on sharia commercial banks - Mirasanti Wahyuni; Fika Azmi (Journal of Islamic Accounting and Finance Research, 2019)
Purpose - This study was conducted to examine the effect of the amount of financing on Non Performing Financing (NPF) and inflation as a moderating variable in sharia commercial banks in Indonesia.Method - This study will be analyzed using the interaction test model, Moderated Regression Analysis (MRA). The population in this study are all Sharia Commercial Banks in Indonesia with sample selection using a purposive sampling method with the requirements of Sharia Commercial Banks (BUS) that have complete data from 2011-2016.Result - The result is all Islamic banking financing has an influence on NPF with inflation as a moderating variable.Implication - This is thought to be influenced by internal bank factors in the form of financing volume and bank external factors in the form of inflation. Then what about the conditions of other Sharia Commercial Banks.Originality - Funding in this study will be divided into financing for profit sharing principles (mudharabah and musyarakah), murabahah, salam, and istishna. The inflation indicator used is CPI.